Pengaruh Akupresure (TITIK LI 4 dan SP 6) Terhadap Durasi Persalinan Kala I Fase Aktif - Yulianti, Indra; Prameswari, Veryudha Eka (Universitas Pahlawan Tuanku Tambusai, 2025)
One intervention that can help speed up the progress of labor is giving acupressure. Providing complementary therapy to birthing mothers is considered safer and has minimal side effects compared to invasive therapy. The acupressure method effectively reduces pain and strengthens contractions, prevents the transmission of harmful stimuli, increases the amount of endorphins in the blood and speeds up the process of labor. If the progress of labor is not handled properly, it can cause birth complications. The aim of the research was to determine the difference between the Li 4 and Sp 6 acupressure points on the duration of the first stage of labor. The research design uses a quantitative descriptive research type with a quasi-experimental design. The sample in this study was 45 respondents. The hypothesis used to test the difference between two means with the right-hand test is the t test if the data distribution is normal with a probability value ≥ 0.05 and if the data distribution is not normal with a probability value < 0.05 then use the Man Whitney test.The research results obtained, Output